The simulation model of IT-product (service) development by a "start-up" company growing inside an academic institution - Lytvynov, V.V.; Saveliev, M.V. (Математичні машини і системи, 2015)
The simulation model of IT-product or service development by a "start-up" company growing inside an academic institution's "business center" is reviewed. The purpose of the model is to estimate final dates of reaching project goals of the "start-up" company. The use of Petri nets for design of such model is shown. An example of model implementation by means of agent simulation is given. Розглядається імітаційна модель розробки IT-продукту або послуги, призначена для оцінки термінів досягнення проектних цілей "start-up" компанією, яка опікається з боку "бізнес-центру" при академічній установі. Відображено застосування мереж Петрі для проектування такої моделі. Наведено приклад реалізації моделі засобами агентного моделювання. Рассматривается имитационная модель разработки IT-продукта или услуги, предназначенная для оценки сроков достижения проектных целей "start-up" компанией, опекаемой со стороны "бизнес-центра" при академическом учреждении. Показано применение сетей Петри для проектирования такой модели. Приведен пример реализации модели средствами агентного моделирования.